Does Lesson Study work? - Cheung, Wai Ming; Wong, Wing Yee (International Journal for Lesson and Learning Studies, 2014)
Purpose – There has been rapid proliferation of Lesson Studies and Learning Studies over the world. Do they really help teachers’ professional development and student learning? The purpose of this paper is to review studies from 2000 to 2010 on Lesson Study and Learning Study to unravel their benefits on teachers and students. Design/methodology/approach – Relevant studies were screen and extracted on available electronic databases to evaluate outcome of Lesson Study and Learning Study. The results were based on nine studies which examined the achievement of Learning Study and Lesson Study. Findings – All reviews identified positive evidence supporting the benefits of Lesson Study and Learning Study as powerful tool to help teachers examine their practices and enhance student learning. Although all nine studies showed positive effects of Lesson Study and Learning Study on teaching, learning or both, different outcome measures were employed and the study designs varied in qualities. Originality/value – Mor...